Measurementof aerodynamiccharacteristics fluxes near thesurface of the body - Исaтaев, М.С.; Молдaбековa, Д.; Омaрaлинa, A.; Есенaлиевa, A.; Сейдуллa, Ж.К. (Recent Contributions to Physics, 2016)
Research of aerodynamics of bluff bodies in the flow of liquids and gases is one of the major issues of industrial aerodynamics. Theseproblems can be attributed to the study of cross-flow constrained the flow of a circular cylinder. The objectives of this work investigation of the effect of the Reynolds number on the flow patterns in the aft area of the cylinder. The studies were conducted in the range of numbers 2
Keywords: jet, aerodynamics, interface, stream, turbulent flow, whirlwind, ideal liquid